Rethinking Serbia Foreign Policy: Case of Open Balkan Initiative and EU Accession - Muhammad Jullyo Bagus Firdaus (JUSS (Jurnal Sosial Soedirman), 2023)
This paper discusses Serbia's position in a multilateral agreement called Open Balkan. The author uses a qualitative method to break down and analyze the narratives from the West and East that impacted Serbia's Foreign Policy trajectory. The leading of Open Balkan economic integration can impact the Berlin Process as a precursor established by European Union, especially for the WB6. The negative response from Kosovo and the unenthusiastic of Montenegro and Bosnia and Herzegovina (BiH) can be a stumbling stone for its members. In addition, to achieve Serbia's national interest, Serbia must be balanced the West and East. In this period Four Pillars Policy is tested. The author discusses the Foreign Policy strategy of Serbia in this issue and balancing defiances with the West and East.